Think India : the rise of the world's next superpower and what it means for every American - Rai, Vinay; Simon, William L., 1930- (New York : Dutton, 2007)
With 1.1 billion residents, the world's largest democracy is poised to dominate the world stage. One of India's wealthiest men gives an insider's view into his country's dynamic transformation, revealing the forces and unique characteristics behind India's meteoric rise. India is not just software, outsourcing, and faraway call centers. With the economy soaring at 8 percent a year, India is a medical and pharmaceutical frontrunner, an R&D powerhouse, a rising manufacturing hub, and an up-and-coming cultural trendsetter in areas from fashion to film. And the world is taking note: Western companies from Lockheed Martin to McDonald's are moving in and research centers for Fortune 500 companies are popping up everywhere. Meanwhile, the U.S. military is forging close ties. Steel tycoon turned educator Vinay Rai, who now runs one of India's two private universities, couples with geopolitical writer Melissa Rossi to map out the rising new India.--From publisher description.
Welcome to India -- What makes India click? : a nation's unparalleled growth -- A slumbering elephant awakens -- India: shaped by its history -- Friends and tigers: the United States, India, and China -- India's growing global muscle -- Understanding Indians: philosophy, attitudes, etiquette -- Incredible India -- A tale of two Indias : the challenges of extreme poverty -- The Indian century.
Includes bibliographical references (p. 259-272) and index.
Keywords: India -- Economic policy -- 1991-; India -- Economic conditions -- 1991-; India -- Foreign economic relations; India -- Commerce